Complete noncompact and stochastically complete m-quasi Yamabe gradient solitons - Giovanni Molica Bisci; Henrique F. de Lima; Ary V. F. Leite; Marco A. L. Velasquez (Electronic Journal of Differential Equations)
We establish new characterization and nonexistence results concerning complete noncompact and stochastically complete m-quasi Yamabe gradient solitons through the applications of a key Bochner type formula jointly with suitable maximum principles dealing, in particular, with the notions of convergence to zero at infinity and polynomial and exponential volume growth.